Charitable Giving by Married Couples: Who Decides and Why Does it Matter? - James Andreoni; Eleanor Brown; Isaac Rischall (Claremont McKenna College, Department of Economics, 2000)
We examine how charitable giving is influenced by who in the household is primarily responsible for giving decisions. Looking first at single-person households, we find men and women to have significantly different tastes for giving, setting up a potential conflict for married couples. We find that, with respect to total giving, married households tend to resolve these conflicts largely in favor of the husband's preferences. Bargaining over charitable giving, rather than letting one spouse take charge, reduces giving by about six percent. When the woman is the decision maker, she will still make a significantly different allocation of those charity dollars, preferring to give to more charities but to give less to each. Our results give new insights into both the demographics of charitable giving and the costliness of household bargaining.
Keywords: 330